A Synergy Between Systems Thinking and Design Thinking: A Case Analysis of the Systems Design Firm IDEO - Cacciatori Morona, Àvaro; Martins, Gleyston Barbosa; Barbosa, Mariana Aono Mendes; Figueiredo, Luiz Fernando Gonçalves de (DAT Journal, 2025)
Design Thinking and Systems Thinking are two sets of theories and guidelines that address the organization and standardization of elements. While Design Thinking is based on the organization of processes in stages and phases in order to solve a problem that involves a context and mainly people, Systems Thinking seeks to understand the relationships of interconnected entities and how they exchange information between themselves and between the environment in which they are inserted. Both premises have similar and complementary guidelines, which can be intertwined through the so-called Systems Design. This work aims to analyze the intertwining between Design Thinking and Systems Thinking through the analysis of two case studies of projects from the company IDEO based on points established through a qualitative and exploratory literary review.